Ibexian-Whiterockian (Ordovician) conodont palaeontology of east and eastern north Greenland - Smith, Michael Paul (1985)
Samples collected from mid-Ibexian (mid-Tremadoc) to late Whiterockian (Llandeilo) of East and eastern North Greenland have yielded a total of 9,725 identifiable conodont clements. The conodonts are referred to 54 multi-element genera and 115 species, new taxa include three genera (Macheticodus, Wandelia and Wcbcrina) and nine species (Eucharodus apion, Macheticodus lekiskus, Multioistodus? celox, Pteracontiodus armillatus, Scalpellodus? narvhalensis, Sibiriodus? kalalekus, Wandelia fuscina, Weberina candidisphaera and Weberina guyi). The faunas are coniform-dominated and generally similar to shallow water, Midcontinent Province faunas found in North America. Some degree of endemicity is indicated by the presence of species found only in the eastern Canadian Arctic Islands and Greenland.